Low lymphozyte pool, colon perforation and hydrocephalus as clinical features in an infant with a postzygotic PIK3CA variant - Léon-Lara, Ximena; Ravens, Sarina; von Hardenberg, Sandra; Auber, Bernd; Bergmann, Anke K.; Ospina, Laura; Guthmann, Florian; Wübbena, Christiane; Brechler, Jan; Weidemann, Jürgen; Richter, Manuela F. (Frontiers in Pediatrics, 2025)
Pathogenic variants in the PIK3CA gene, which encodes the p110-α catalytic subunit of the phosphoinositide 3-kinase (PI3K), are commonly associated with overgrowth syndromes and cancer. We report a patient with the point variant c.1030G>A p.(Val344Met) in the PIK3CA gene who presented shortly after birth with viral sepsis and and severe lymphopenia, followed by colonic perforations. Histopathology showed ulcerative necrotizing colitis with lymphatic vascular malformation. The patient subsequently developed hydrocephalus requiring a ventriculoperitoneal shunt, complicated by refractory ascites that resolved with acetazolamide therapy. Awareness of the potential disease spectrum through early molecular diagnosis, combined with a comprehensive immunologic evaluation, enabled individualized management via closer clinical monitoring and timely interventions to prevent and control neurological and infectious complications. This case highlights the phenotypic heterogeneity of PIK3CA pathogenic variants and the importance of early precision medicine in pediatric care.